2006
DOI: 10.1097/01.mlr.0000188915.66942.69
|View full text |Cite
|
Sign up to set email alerts
|

Gender Disparities in Percutaneous Coronary Interventions for Acute Myocardial Infarction in Pennsylvania

Abstract: These results suggest that the morbidity and mortality associated with AMI in women could be reduced by increased use of PCI and that more women admitted for AMI should receive consideration for PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 48 publications
(27 reference statements)
2
25
1
Order By: Relevance
“…Indeed, Tavris's study 1 complements previous studies that have reported gender-related differences in survival-to-hospital-discharge rates for cardiac arrest 2 and ST-segment elevation myocardial infarction (STEMI) patients 3,4 that may be partially attributed to receiving different in-hospital medications and procedures or inequity in access to care. 2 -4 Women are less likely to have their myocardial infarction (MI) diagnosed in the emergency department, and are less likely to receive invasive diagnostics 5 -7 and treatment such as percutaneous coronary intervention (PCI) (23.9% women vs 39.9% men), 3,4 which may account for poorer outcomes 6,7 and increased mortality with MI (12.7% in women vs 9.7% in men). 3,4 Women had 24% lower odds of receiving PCI when they were taken to hospitals with PCI availability.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, Tavris's study 1 complements previous studies that have reported gender-related differences in survival-to-hospital-discharge rates for cardiac arrest 2 and ST-segment elevation myocardial infarction (STEMI) patients 3,4 that may be partially attributed to receiving different in-hospital medications and procedures or inequity in access to care. 2 -4 Women are less likely to have their myocardial infarction (MI) diagnosed in the emergency department, and are less likely to receive invasive diagnostics 5 -7 and treatment such as percutaneous coronary intervention (PCI) (23.9% women vs 39.9% men), 3,4 which may account for poorer outcomes 6,7 and increased mortality with MI (12.7% in women vs 9.7% in men). 3,4 Women had 24% lower odds of receiving PCI when they were taken to hospitals with PCI availability.…”
mentioning
confidence: 99%
“…2 -4 Women are less likely to have their myocardial infarction (MI) diagnosed in the emergency department, and are less likely to receive invasive diagnostics 5 -7 and treatment such as percutaneous coronary intervention (PCI) (23.9% women vs 39.9% men), 3,4 which may account for poorer outcomes 6,7 and increased mortality with MI (12.7% in women vs 9.7% in men). 3,4 Women had 24% lower odds of receiving PCI when they were taken to hospitals with PCI availability. 4 Even more impressive is the fact that when women received the PCI intervention, the difference in mortality rates between genders disappeared.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15][16][17][18][19][20][21] For example, women are more likely to have a diagnosis of myocardial infarction missed in the Emergency Department, and are less likely to receive invasive diagnostic testing and treatments for cardiovascular diseases, such as cardiac catheterization and percutaneous coronary intervention -all of which might account for poorer outcomes and increased mortality. 5,17,[22][23][24][25][26][27] Previous research on age and gender-based out of hospital cardiac arrest (OHCA) has shown contradictory findings. 2,3,6,[28][29][30][31][32] Kannel et al, reported lower rates of sudden cardiac arrest in women when compared to men.…”
Section: Introductionmentioning
confidence: 99%